The Rhetoric of Disability on Instagram: A Post-Qualitative Photographic Analysis - Parra Gomez, Sheila (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Social networks, such as Instagram, have flourished samples of realistic images of disability produced by the group itself, offering a discourse that is different from the traditional one, more radical and diverse. This work, through a post-qualitative photographic analysis of 100 photographs from 54 Instagram profiles, seeks to define a new rhetoric of disability to update the rhetoric of disability proposed by Garland-Thomson (2001), but in the 3.0 web. The new classifications speak of emancipation, sexuality, happiness, super-capacity, rebellion and pride, in order to normalize the group and allow its inclusion and equality.